Chirema Chine Mazano Chinotamba Chakazendama Madziro - Mapondera, Wallen (Rhodes University, Faculty of Humanities, Department of Fine Art, 2020)
This mini-thesis has developed as a practice-based supporting document to the exhibition Chirema Chine Mazano Chinotamba Chakazendama Madziro. The exhibition responds to how people become innovative in finding alternative means of survival and staying relevant in an economically depressed country. Zimbabwe is often the first country that comes to mind when people talk about hyperinflation; the situation was and still is intolerable, but somehow its citizens find means to pull through. Unemployment and poverty are the main causes of physical and mental problems for an individual. With this thesis, I highlight the innovations employed by Zimbabweans as a way of keeping themselves busy. I approach this through analysing the Zimbabwean general public's creative reactions, and by tracing Zimbabwean visual artists' use of found objects as a reaction to the country's economic hardships. As people have been pushed to find alternative ways of survival, Zimbabwean artists in particular also shifted from using conventional art materials due to their unavailability. They began to redefine what art material is by employing objects in their artworks that previously had a non-art function. As such, there is a growing need to recognise, classify and document the shifts and establish platforms to generate growth of these innovations. In this minithesis I discuss my own practice, and I analyse the works of Moffat Takadiwa, Gareth Nyandoro and Serge Attiku Clottey.
Keywords: Art, Zimbabwean; Art -- Economic aspects -- Zimbabwe; Artists -- Zimbabwe; Takadiwa, Moffet; Nyandoro, Gareth; Clottey, Serge Attiku; Mapondera, Wallen -- Exhibitions